2017
DOI: 10.1253/circj.cj-16-0942
|View full text |Cite
|
Sign up to set email alerts
|

Higher Body Mass Index Increases Risk of HeartMate II Pump Thrombosis But Does Not Adversely Affect Long-Term Survival

Abstract: Background: Obesity has been correlated with various adverse events in patients who receive left ventricular assist devices (LVAD). In this study, we sought to further characterize the role of obesity in this patient population. Methods and Results:We performed a retrospective analysis of 164 patients implanted with a HeartMate II from August 2008 to December 2014. Patients were categorized into 2 BMI groups based on WHO guidelines: BMI 18.5-30 kg/m 2 (n=99) and BMI >30 kg/m 2 (n=65). Patient demographics, adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…Our work confirms the results of several recent studies, which failed to detect a significant difference in short‐term and intermediate postoperative survival between obese and nonobese LVAD recipients . However, higher rates of hospital readmissions and complications such as AKI , infection , thromboembolism , and PT are often present in the obese cohort. We observed higher rates of stage 2/3 AKI and PT in the extremely obese cohort, which is in agreement with prior studies .…”
Section: Discussionsupporting
confidence: 90%
“…Our work confirms the results of several recent studies, which failed to detect a significant difference in short‐term and intermediate postoperative survival between obese and nonobese LVAD recipients . However, higher rates of hospital readmissions and complications such as AKI , infection , thromboembolism , and PT are often present in the obese cohort. We observed higher rates of stage 2/3 AKI and PT in the extremely obese cohort, which is in agreement with prior studies .…”
Section: Discussionsupporting
confidence: 90%
“…While LVADs are an effective long-term intervention for end-stage heart failure, expanding rates of obesity and extreme obesity increasingly complicate patient selection for this advanced surgical therapy (5,6,11). Though previous data and guidelines have suggested that LVAD implantation in patients with very low or very high BMI may confer excessive risk, several recent reports indicate no increased mortality in obese patients implanted with LVADs (5,(7)(8)(9)(10)(11)(12). This study evaluated outcomes in a group of patients with extreme obesity, including 25 patients with BMI greater than 40 kg/m 2 and 4 with BMI greater than 50 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that obese patients may have increased rates of LVAD thrombosis and infections, but have survival rates similar to normal and underweight patients. These reports have generated varied results, and as a result, selection and management of LVAD patients with high BMIs remains challenging (7)(8)(9). At present there is only one other published study which investigated outcomes in patients with BMI ≥35 kg/m 2 (10).…”
Section: Original Articlementioning
confidence: 99%
“…Recently, obesity was reported to be a risk factor of device thrombosis. While the mechanism is unclear, Han et al proposed that obese patients have a higher risk of developing blood clots and that obesity may interfere with optimal device placement or remodeling …”
Section: Discussionmentioning
confidence: 99%